Furniture Construction Skill Gap Analysis among Technical College Teachers in Zamfara and Katsina States - Maryam Sanni Mannir; Mohammed Maik Bala; Abdullahi Muhammad Hassan (Jurnal Pendidikan Teknologi dan Kejuruan, 2020)
This study identified the practical skills possessed and skills required by furniture construction teachers in Zamfara and Katsina State, Nigeria. Three research questions that sort to determine the skills needs of furniture construction teachers were answered and one hypothesis was tested at 0.05 level of significance. A descriptive survey research design was adopted for the study. The population for the study was 42 teachers. A structured questionnaire was used to gather data from the 42 woodwork furniture construction teachers. The instrument had a reliability coefficient of 0.89 using Cronbach Alpa statistic.  Mean and standard deviation was used to answer research questions and a t-test was used to test the hypothesis using the IBM SPSS version 20. The findings of the study revealed that the respondents require skills on the ability to hold a saw with fore-finger straight out on one side of the handle, the ability to follow the “FEWTEL” method in preparing a piece of wood require further training, setting sliding bevel when marking out dovetail joint and selection of the right adhesive according to the purpose and type of wood as well as amount of force the adhesive would be subjected to required skills. It was recommended that; government should provide opportunities for furniture construction teachers to go on further training on the modern furniture construction technology required. The identified skills required by teachers of furniture construction should form the basis for the up-skill workshop to be organized as in-house training.